Perlindungan Hukum Investor pada Fintech Peer-To-Peer Lending Syariah di Indonesia: Analisis Integratif Hukum Positif dan Prinsip Maslahah Mursalah - Nurul Novianti Azzahra; Maman Surahman; Liza Dzulhijjah (Bandung Conference Series: Sharia Economic Law)
Abstract. The rapid growth of sharia peer-to-peer (P2P) lending in Indonesia, alongside a series of default cases affecting both conventional and sharia-labelled platforms, raises concern over the extent to which investors are genuinely protected under current regulation. This study aims to analyze the form of legal protection provided to investors in the practice of sharia P2P lending in Indonesia, and to formulate an ideal concept of investor protection viewed from positive law and the principle of maslahah mursalah. The research employs a qualitative method with a normative-juridical and conceptual approach, using primary, secondary, and tertiary legal materials as the main data, supplemented by a semi-structured interview with the Financial Services Authority (OJK) as complementary and validating data. Findings show that investors are legally positioned as unsecured (concurrent) creditors without special collateral, and that preventive and repressive protection mechanisms already exist but remain substantively weak, particularly the Sharia Supervisory Board's oversight, which is still largely administrative, alongside the absence of a systemic compensation scheme and a lex specialis regulation. Evaluated against Al-Qaradawi's three conditions of maslahah mursalah, the existing regulation formally satisfies the requirements, yet its real effectiveness still falls short of the intended sharia benefit. The study proposes an integrative six-pillar framework combining positive law and maslahah mursalah to strengthen investor protection in Indonesia's sharia fintech ecosystem. Abstrak. Pertumbuhan pesat fintech peer-to-peer (P2P) lending syariah di Indonesia, yang diiringi rangkaian kasus gagal bayar pada penyelenggara konvensional maupun berlabel syariah, menimbulkan pertanyaan mengenai sejauh mana investor benar-benar terlindungi oleh regulasi yang berlaku saat ini. Penelitian ini bertujuan untuk menganalisis bentuk perlindungan hukum yang diberikan kepada investor dalam praktik penyelenggaraan fintech P2P lending syariah di Indonesia, serta merumuskan konsep perlindungan hukum yang ideal ditinjau dari hukum positif dan prinsip maslahah mursalah. Penelitian menggunakan metode kualitatif dengan pendekatan yuridis normatif dan konseptual, menggunakan bahan hukum primer, sekunder, dan tersier sebagai data utama, dilengkapi wawancara semi terstruktur dengan Otoritas Jasa Keuangan (OJK) sebagai data pelengkap dan validasi. Hasil penelitian menunjukkan bahwa investor berkedudukan hukum sebagai kreditur konkuren tanpa jaminan khusus, dan bahwa mekanisme perlindungan preventif maupun represif sudah tersedia namun masih lemah secara substantif, terutama pada pengawasan Dewan Pengawas Syariah yang masih bersifat administratif, serta belum tersedianya skema kompensasi sistemik dan regulasi yang bersifat lex specialis. Dievaluasi melalui tiga syarat maslahah mursalah Al-Qaradawi, regulasi yang ada secara formal telah memenuhi persyaratan tersebut, namun efektivitas riilnya masih jauh dari kemaslahatan syariah yang dikehendaki. Penelitian ini mengusulkan kerangka integratif enam pilar yang memadukan hukum positif dan maslahah mursalah untuk memperkuat perlindungan investor pada ekosistem fintech syariah di Indonesia.